2017
DOI: 10.1016/j.soard.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect by which gastric plication and sleeve gastrectomy procedures alter metabolic and physical parameters in an obese type 2 diabetes rodent model

Abstract: The GP and SG procedures have the same effectiveness and can help improve diabetes control by regulating weight, glucose tolerance, and metabolic hormones and augmenting gastrointestinal dynamics. Therefore, these procedures have great potential as therapies for obesity and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Weight loss is the commonest outcome, by which the efficacy of a bariatric procedure is estimated. Based on animal studies, gastric plication and sleeve gastrectomy displayed the same efficacy, concerning weight loss, reduced food intake fasting plasma glucose and intraperitoneal glucose tolerance test, and both procedures affected ghrelin and GLP-1 levels [ 53 ]. Although gastric plication has functional restrictive effects [ 54 ], sleeve gastrectomy affects residual gastric volume, gastrointestinal tract motility, and hormonal balance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss is the commonest outcome, by which the efficacy of a bariatric procedure is estimated. Based on animal studies, gastric plication and sleeve gastrectomy displayed the same efficacy, concerning weight loss, reduced food intake fasting plasma glucose and intraperitoneal glucose tolerance test, and both procedures affected ghrelin and GLP-1 levels [ 53 ]. Although gastric plication has functional restrictive effects [ 54 ], sleeve gastrectomy affects residual gastric volume, gastrointestinal tract motility, and hormonal balance [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, food consumption is substantially reduced. Some studies demonstrated that bariatric surgery, including SG and Roux-en-Y gastric bypass, was able to reduce food intake after the operation in rat models [16,17].…”
Section: Reduced Food Intakementioning
confidence: 99%
“…The secretion and change in the glucose level, leptin hormone, and insulin will induce the expression of orexigenic molecules in the NPY/AgRP neurons [42]. Previous studies indicated that the SG procedure was capable of improving glucose tolerance and insulin sensitivity, and reducing food intake, which provides a therapeutic approach to the treatment of T2D [16,43]. SG significantly modifies intestinal permeability without impairing the glucose homeostasis improvement induced by SG [44].…”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation